Impact of Nickel and Lead Exposure on the Phytochemical Composition and Bioactive Compounds of Justicia Adhatoda Leaves - Chowbey, Anita; Rehman, Farha (Journal of Neonatal Surgery, 2025)
This study investigates the impact of heavy metals, specifically nickel and lead, on the yield, phytochemical composition, and bioactive compound content of Justicia adhatoda leaves. The plant extracts were subjected to hydroalcoholic and petroleum ether extraction methods, and the yield was assessed after treatment with different concentrations of nickel and lead (50mg, 100mg, 150mg) for 45 days. The phytochemical analysis revealed that flavonoids, phenols, saponins, and alkaloids were present in the control group, with changes observed after metal exposure. The total flavonoid content (TFC) and total phenolic content (TPC) decreased with increasing metal concentrations, particularly under lead exposure. High-Performance Liquid Chromatography (HPLC) analysis identified quercetin as a key bioactive compound, and its concentration was found to decrease with both nickel and lead exposure, with lead showing a more pronounced reduction. Despite these changes, the study highlights the plant’s resilience to nickel exposure, which showed a milder impact on bioactive compound levels compared to lead. The findings suggest that environmental pollution, particularly from lead, may significantly compromise the medicinal potential of Justicia adhatoda, while nickel exposure has a relatively lesser effect on its bioactive content.